2021
DOI: 10.3390/cancers13122970
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro 3D Cultures to Model the Tumor Microenvironment

Abstract: It is now well established that the tumor microenvironment plays a key role in determining cancer growth, metastasis and drug resistance. Thus, it is fundamental to understand how cancer cells interact and communicate with their stroma and how this crosstalk regulates disease initiation and progression. In this setting, 3D cell cultures have gained a lot of interest in the last two decades, due to their ability to better recapitulate the complexity of tumor microenvironment and therefore to bridge the gap betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 125 publications
1
42
0
Order By: Relevance
“…Next, PFs and CAFs used in this study were not patientmatched, therefore using CAFs from different patient donors would have been desirable. Prospectively, it would be interesting to investigate the PDAC SiaJ in a co-culture system, as the interaction between cancer cells, immune cells, and fibroblasts is extremely important and could influence different treatment strategies [87,88]. In addition, culture cells in other ECM-specific substrates might influence cell phenotype [89].…”
Section: Discussionmentioning
confidence: 99%
“…Next, PFs and CAFs used in this study were not patientmatched, therefore using CAFs from different patient donors would have been desirable. Prospectively, it would be interesting to investigate the PDAC SiaJ in a co-culture system, as the interaction between cancer cells, immune cells, and fibroblasts is extremely important and could influence different treatment strategies [87,88]. In addition, culture cells in other ECM-specific substrates might influence cell phenotype [89].…”
Section: Discussionmentioning
confidence: 99%
“…There are some data about the treatment sensitivity differences of these models, which highlight that 3D structures and cellular complexity could influence the experimental results of in vitro therapeutic drug sensitivity tests [51,55]. Gene expression analyses data from these 2D vs. 3D spheroid cultures described some well-known and expected alterations in glycolysis, PI3K/Akt pathways and/or ECM protein and other metabolic events (e.g., mitophagy) and highlighted the importance of metabolic rewiring differences in the used in vitro models [51,55,56]. The cellular and ECM heterogeneity could have particular significance in immune-oncology drug tests and their in vitro experiments in future studies, as several papers suggested [52,53].…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, we found that TAM heterogeneity is lost when isolated and cultured ex vivo in 2D conditions, emphasizing the need for TME signals to maintain their identity. In recent years, 3D cultures in hydrogels, including collagen [ 55 , 56 ], have provided valuable tools to accelerate tumor studies and TME modeling [ 33 , 34 ]. In the present study, we developed a 3D collagen co-culture system to mimic the melanoma TME and investigate how interactions between melanoma cells, fibroblasts, and macrophages shape the early stages of macrophage immune activity leading to such complex phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that organotypic melanoma cultures outperform 2D assays when studying TME-imprinting mechanisms and closely resemble tumor growth as observed in human lesions while supporting cell survival and function [ 32 , 33 ]. The use of 3D cultures may accelerate the identification of predictive and/or prognostic markers and the development of effective combination therapies [ 34 ]. Ex vivo systems that incorporate key features of the native TME and model the dynamic response to checkpoint inhibitors can facilitate efforts in precision immuno-oncology.…”
Section: Introductionmentioning
confidence: 99%